233 A Closed-Loop Audit Assessing the Compliance of General Surgery Department in Completing Treatment Escalation Plan (TEP). (28th February 2022) - Lee, L.; Parmar, C.; Allen, C.
Abstract: Aim: In the event of clinical deterioration, a treatment escalation plan describes individualized interventions that would be appropriate for a patient. Likewise, it allows clear communication amongst staff members and the patient about the limits of treatment. This audit aimed to evaluate the compliance of the General Surgery department during the pandemic. Method: A closed-loop audit was conducted by looking at notes of General Surgery patients retrospectively and identifying those who's had their treatment escalation plan form filled out during their admission. Data were collated, analysed, and presented in our local audit meeting. Thereafter, we disseminated the results to the department and modified our admission clerking proforma to ensure this is done. Afterwards, a re-audit was done to assess the improvement of compliance. Results: A total of 24 patients were included. Before the modification of the clerking proforma, only 21% of TEP were completed. After the added changes, 36% of admitted patients had their form completed. Conclusions: Our department was generally doing poorly with regards to ensuring our patients had TEP forms completed. Even though we generally have young, fit and well patients, according to our trust guidelines, all patients are meant to have their forms filled out. This ensures clear communication among staff and proper allocation of resources if there will be any shortages in the services that could be provided. By shining light on this topic, our department had been more compliant and proactive with ensuring that patients, especially the elderly, had a TEP form filled out.